Case report: Post-COVID new-onset neurocognitive decline with bilateral mesial-temporal hypometabolism in two previously healthy sisters - Fabrizio Cocciolillo; Daniela Pia Rosaria Chieffo; Daniela Pia Rosaria Chieffo; Alessandro Giordano; Alessandro Giordano; Valentina Arcangeli; Ilaria Lazzareschi; Rosa Morello; Giuseppe Zampino; Piero Valentini; Danilo Buonsenso; Danilo Buonsenso (Frontiers Media S.A., 2023)
BackgroundLong coronavirus disease (COVID) is increasingly recognized in adults and children; however, it is still poorly characterized from a clinical and diagnostic perspective, particularly in the younger populations.Case presentationWe described the story of two sisters-with high social and academic performance before their severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection-who reported severe neurocognitive problems, initially classified as psychologic pandemic distress and eventually found to have significant brain hypometabolism.ConclusionsWe provided a detailed clinical presentation of neurocognitive symptoms in two sisters with long COVID associated with brain hypometabolism documented in both sisters. We believe that the evidence of objective findings in these children further supports the hypothesis that organic events cause persisting symptoms in a cohort of children after SARS-CoV-2 infection. Such findings highlight the importance of discovering diagnostics and therapeutics.